1988
DOI: 10.1161/01.cir.78.2.473
|View full text |Cite
|
Sign up to set email alerts
|

Therapy to reduce free radicals during early reperfusion does not limit the size of myocardial infarcts caused by 90 minutes of ischemia in dogs.

Abstract: It has been postulated that oxygen-centered free radicals are produced in significant quantities upon reperfusion of ischemic myocardium and could cause the death of myocytes that are still reversibly injured at the end of ischemia ("reperfusion injury"). However, we have shown previously that anti-free radical therapies including superoxide dismutase (SOD) and inhibitors of xanthine oxidase did not limit infarct size after 40 minutes of ischemia and 4 days of reperfusion in dogs. To test whether 40 minutes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
2
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 28 publications
0
40
2
2
Order By: Relevance
“…15 The regression lines between infarct size and collateral blood flow obtained in these two studies were superimposable with similar scatter. These observations suggest that 1) the methods of estimating infarct size in the present study were reliable and 2) most, if not all, of the myocyte death that is observed after 90 minutes of ischemia and 4 days of reperfusion has already occurred by the end of the first hour of reperfusion.…”
Section: Myocardial Blood Flowmentioning
confidence: 56%
See 2 more Smart Citations
“…15 The regression lines between infarct size and collateral blood flow obtained in these two studies were superimposable with similar scatter. These observations suggest that 1) the methods of estimating infarct size in the present study were reliable and 2) most, if not all, of the myocyte death that is observed after 90 minutes of ischemia and 4 days of reperfusion has already occurred by the end of the first hour of reperfusion.…”
Section: Myocardial Blood Flowmentioning
confidence: 56%
“…Conversely, in a similar study, also of reperfusion after 90 minutes of ischemia, but in which no critical stenosis was used, we found no effect of SOD and catalase on infarct size. 15 The difference in the mode of reperfusion is a possible reason for these discrepant results. A critical stenosis could exacerbate reperfusion injury, for example, by slowing blood velocity, increasing PMN adhesion to endothelium, and thereby increasing free radical production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators found similar beneficial effects of antioxidant interventions in experimental models of myocardial infarction. However, there is a significant number of studies describing a failure of antioxidants to prevent injury, or demonstrating an early protective effect, that waned with increased duration of reperfusion [63,64]. Transgenic mice that overexpress copper, zinc superoxide dismutase (SOD1) exhibited significant protection from postischemic injury [65].…”
Section: Generation Of Reactive Oxygen Species (Ros) and The Post-infmentioning
confidence: 99%
“…Explosive myocardial swelling, calcium overload, and release of toxic oxygen-derived free radicals are the mechanisms most frequently implicated in the genesis of reperfusion-induced extension of necrosis.1-4 The conclusion that free radicals extend necrosis is based on reports of marked reductions in infarct size by free radical scavengers administered just before or during reperfusion.5-18 However, other investigators, using the same agents in the same mode, were unable to demonstrate a reduction in infarct size. [19][20][21][22][23][24][25][26][27][28][29][30] The role of explosive myocardial swelling and calcium overload is also controversial because many consider these changes to be the consequences rather than the causes of myocardial necrosis. 31,32 The controversy concerning the mechanisms and treatments of reperfusion-induced extension of necrosis is compounded by the fact that there is no See p 1070 direct and unequivocal evidence that reperfusion does extend necrosis.…”
mentioning
confidence: 99%